Determinan Internal Harga Saham Perusahaan Bumn Non Bank yang Terdaftar di Bursa Efek Indonesia - ., Endri (Ultimaccounting Jurnal Ilmu Akuntansi, 2018)
The capital market is a place for companies to raise capital by offering shares to the public. Fundamental analysis believe that the performance of the company issuing the shares will greatly affect a company's value. By By Keputusan Menteri Badan Usaha Milik Negara Nomor: KEP-100/MBU/2002 has set the terms of the provisions of the company's performance seen over the soundness of State-Owned Enterprises.The results showed (1) Return On Equity (ROE) partially has a positive and significant impact on stock prices, (2) Return on Investment (ROI) partially has a negative and significant impact on stock prices, (3) Cash Ratio partially has a positive and significant impact on stock prices, (4) Current Ratio partially has a positive and significant impact on stock prices, (5) Collection Periods (CP) partially has a negative and significant impact on stock prices, (6) Inventory Turnover (PP) partially has a positive and significant impact on stock prices, (7) Total Asset Turnover (TATO) partially has a negative and significant impact on stock prices, (8) Total Equity against Total Assets (TMS against TA) partially have positive and significant impact on stock prices, and (9) Return on Equity (ROE, Return on Investment (ROI), Cash Ratio, Current Ratio, collecti on Periods (CP), Inventory Turnover (PP), Total Asset Turnover (TATO) and Total Equity Against TA (TA TMS) have a simultaneous effect on on stock price. Keywords: Stock prices, financial performance, data panel regression model, State-Owned Enterprises